2020
DOI: 10.33021/icfbe.v1i1.1373
|View full text |Cite
|
Sign up to set email alerts
|

Green Is the New Black: The Role of Green Marketing Awareness and Perceived Innovation in the Fast Fashion Industry

Abstract: <p>The purpose-driven strategy has become one of the tactics used by companies as a competitive advantage to attract the market. The growing interest of sustainability and ecofriendly products can be seen among the younger consumer's behaviour, which indicated the increase of their awareness of the recent phenomena. The current study examined the effect of green marketing awareness and perceived innovation on customer's purchase intention by considering the corporate image, product image, and purchase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
1
2
0
1
Order By: Relevance
“…As thing stand, it is clearly helpful The Body Shop to promotes their product automatically through word of mouth. This result is in line with the study of Arham and Dwita (2021), then Tulangow (2020), which stated that green brand innovative has a significant impact on green brand loyalty (Arham & Dwita, 2021;Tulangow, 2020).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…As thing stand, it is clearly helpful The Body Shop to promotes their product automatically through word of mouth. This result is in line with the study of Arham and Dwita (2021), then Tulangow (2020), which stated that green brand innovative has a significant impact on green brand loyalty (Arham & Dwita, 2021;Tulangow, 2020).…”
Section: Resultssupporting
confidence: 89%
“…Green brand loyalty is created by the fulfillment of consumer expectations consistently, especially for cosmetic products that often chemical-based materials (Lin et al, 2017). A number of studies have found several factors that greatly affect green brand loyalty, including green brand innovativeness and green perceived value (Tulangow, 2020), in which these factors can be stated as evidence of growing consumer expectations for eco-friendly cosmetic products (Zulfikar dan Mayvita, 2018). At this time, consumers not only want ecofriendly cosmetic products, but most of them also want products that are unique, innovative, and have many benefits, or have values that match their expectations.…”
Section: Introductionmentioning
confidence: 99%
“…Bununla birlikte işletmelerin ve tüketicilerin çevresel farkındalıklarının artmasıyla birlikte ekolojik, sürdürülebilir yeniliklere olan ilgi de artmaktadır. Araştırmalarda; çevreci yeniliklerin imajı arttırdığı da ortaya konmaktadır (Chen, 2008;Chen, 2010;Kang, & Hur, 2012;Amores-Salvadó vd., 2014;Ng vd., 2014;Huang vd., 2016;Tulangow & Kusumawardani, 2020).…”
Section: Algılanan Yenilikçilik Ve Marka ġMajı ġLiģkisiunclassified
“…According to Kim et al (2017), the brand image also shows how customer perception towards a brand will permanently be engraved in the customer's memory. A brand with a good image will usually be more favourable and gain more advantages in the market, such as strengthening its position and performance, and protecting the brand from rivalry (Nyadzayo & Khajehzadeh, 2016;Tulangow & Kusumawardani, 2020).…”
Section: Brand Imagementioning
confidence: 99%